2008
DOI: 10.2144/000112673
|View full text |Cite
|
Sign up to set email alerts
|

A Microfluidic System for Dynamic Yeast Cell Imaging

Abstract: The investigation of cellular processes and gene regulatory networks within living cells requires the development of improved technology for dynamic, single cell imaging. Here, we demonstrate a microfluidic system capable of mechanical trapping of yeast cells with continuous flow and flow switching capability during time-lapse high magnification fluorescence imaging. The novel functionality of the system was validated by observing the response of pheromone-induced expression of GFP in Saccharomyces cerevisiae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
58
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 14 publications
1
58
0
Order By: Relevance
“…The development of microfluidic devices has raised expectations for their capability to cultivate yeast cells in controlled environments with continuous microscopic observation (14,15). Unfortunately, none of the currently existing microfluidic devices can be applied for long-term replicative aging studies.…”
Section: Saccharomyces Cerevisiaementioning
confidence: 99%
“…The development of microfluidic devices has raised expectations for their capability to cultivate yeast cells in controlled environments with continuous microscopic observation (14,15). Unfortunately, none of the currently existing microfluidic devices can be applied for long-term replicative aging studies.…”
Section: Saccharomyces Cerevisiaementioning
confidence: 99%
“…Lee et al reported a microfluidic chip with a passive filtering-and-trapping mechanism that is capable of fixing cells in the same focal plane for image without any moving components on the chip. 9 Ohnuki et al developed an active cell trapping mechanism that uses flexible partical desportin mass spectrometry membranes to hold cells stationary in the same focal plane. 6 However, both designs lack the ability to isolate or manipulate single yeast cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, manual manipulation of cells is laborious, and accurately determining pedigree and protein expression by microscopy is challenging as cells grow out of the focal plane after only a few divisions. Various microfluidic devices maintain cells in a single focal plane as they grow (10,(16)(17)(18)(19)(20)(21), but many of these devices require sophisticated fabrication techniques such as multilayer fabrication with valves (16,18), channel height differences (17), or membranes (10,21). To optimize the statistical power of these techniques, the initial placement of cells should be controlled; several other microfluidic devices achieve single-cell trapping (22)(23)(24), but these trapping mechanisms are not conducive to the lineage analysis that we perform here.…”
mentioning
confidence: 99%